The new triple-helix policy of Lombardy region: evidence from nine innovation clusters. (6th March 2019) - Giusti, Jessica D.; Ferrario, Stefania; Belfanti, Federica; Alberti, Fernando G.
Innovation clusters represent a concerted effort to bring together research, industry and government in line with the triple-helix framework. Clusters affect and are affected by their regional context where they are located. From this perspective, clusters are regarded as an integral part of regional innovation systems. A regional renewal based on innovation clusters may end up into incremental change, diversification or radical change and may involve the regional government, regional clusters association and cluster organisations. Nevertheless, little is known about how regions drive the implementation of renewal policies based on innovation clusters, differentiating among regional development paths and levels of regional governance. Hence, we collected data according to an embedded comparative case study research design on Lombardy region, where the regional government promoted a triple-helix inspired policy of implementing nine innovation clusters. Findings have both conceptual and policy implications with regard to triple-helix, clusters and regional innovation systems.